COMPARISON OF INVASIVE VERSUS MEDICAL STRATEGY OF PATIENTS WITH NON-ST ELEVATION MYOCARDIAL INFARCTION WITH INTERMEDIATE THROMBOLYSIS IN MYOCARDIAL INFARCTION SCORE - SHOUKAT , M; SHAKEEL , AA; ULLAH , N; QURESHI , AE; RAHI , MN; SHAFI , T (Biological and Clinical Sciences Research Journal, 2023)
Non-ST-elevation myocardial infarction (NSTEMI) and unstable angina pectoris are frequent causes of hospital admission in the elderly. However, clinical trials targeting this population are scarce, making these patients less likely to receive treatment according to guidelines. This study was designed to compare the outcome of invasive versus a medical strategy of patients with non-ST elevation myocardial infarction with intermediate Thrombolysis in Myocardial Infarction score. This study was conducted at the Department of Cardiology, Rehmatul lil Alameen Institute of Cardiology, Lahore, from 21-5-2019 to 21-11-2019. A total of 220 (110 patients in each group) patients fulfilling inclusion criteria from emergencies were recruited. Then patients were randomly divided into two groups by using the lottery method. In group A, patients were managed through an invasive strategy. In group B, patients underwent medication only. Patients in the invasive strategy underwent percutaneous coronary intervention, or coronary artery bypass graft patients in the medical strategy group were given standard medical management per hospital protocol. Then patients were followed up there for 3 days. After 3 days, patients were discharged and were followed up in OPD for 30 days. It was noted if the patient presented again in an emergency with recurrent myocardial infarction (MI) or if death occurred within 30 days. This study compared an invasive and medical strategy in NSTEMI patients regarding recurrent MI and mortality within 30 days. According to the findings of this study, no significant difference was seen in recurrent MI (Group-A: 13.6% & Group-B: 12.7%, p-value=0.84) in both groups, but mortality (Group-A: 10.9% & Group-B: 3.6%, p-value=0.037) was significantly higher in patients who underwent invasive strategy. Considering the results of this study, it can be concluded that NSTEMI patients treated with conservative treatment had a low mortality rate and fewer chances of recurrent MI.